Improvement Scheme of Switchover Control System without Blowing-out of Mine Main Ventilator - MENG Lin-shan; MA Xiao-ping; LI Quan-bao (Gong-kuang zidonghua, 2012)
For the problem that industrial computer is easy to crash after a certain number of years in switchover control system without blowing-out of mine main ventilator, the paper proposed the solution of connecting sensor to the switch, and using multiple industrial computers to read data at the same time. For the problem that RS485 signal output by temperature logging devices and electrical parameters acquisition modules cannot directly access the switch, the paper proposed two improvement schemes, namely adding serial servers or RS485 modules of PLC. It analyzed advantages and disadvantages of the schemes and ultimately chose the scheme of adding RS485 module of PLC. The practical application shows that the improved system runs well and achieves the desired effect.